Elevated fluid and glycosaminoglycan content in the Achilles tendon contribute to higher intratendinous pressures: Implications for Achilles tendinopathy - Lauren Pringels; Gert-Jan Van Valckenborgh; Patrick Segers; Amélie Chevalier; Hedwig Stepman; Evi Wezenbeek; Arne Burssens; Luc Vanden Bossche (Elsevier, 2024)
Background: Tendinopathy alters the compositional properties of the Achilles tendon by increasing fluid and glycosaminoglycan content. It has been speculated that these changes may affect intratendinous pressure, but the extent of this relationship remains unclear. Therefore, we aimed to investigate the impact of elevated fluid and glycosaminoglycan content on Achilles tendon intratendinous pressure and to determine whether hyaluronidase (HYAL) therapy can intervene in this potential relationship. Methods: Twenty paired fresh-frozen cadaveric Achilles tendons were mounted in a tensile-testing machine and loaded up to 5% strain. Intratendinous resting (at 0% strain) and dynamic pressure (at 5% strain) were assessed using the microcapillary infusion technique. First, intratendinous pressure was measured under native conditions before and after infusion of 2 mL physiological saline. Next, 80 mg of glycosaminoglycans were administered bilaterally to the paired tendons. The right tendons were additionally treated with 1500 units of HYAL. Finally, both groups were retested, and the glycosaminoglycan content was analyzed. Results: It was found that both elevated fluid and glycosaminoglycan content resulted in higher intratendinous resting and dynamic pressures (p < 0.001). HYAL treatment induced a 2.3-fold reduction in glycosaminoglycan content (p = 0.002) and restored intratendinous pressures. Conclusion: The results of this study demonstrated that elevated fluid and glycosaminoglycan content in Achilles tendinopathy contribute to increased intratendinous resting and dynamic pressures, which can be explained by the associated increased volume and reduced permeability of the tendon matrix, respectively. HYAL degrades glycosaminoglycans sufficiently to lower intratendinous pressures and may, therefore, serve as a promising treatment.